In Vivo Confocal Microscopy Observation of Cell and Nerve Density in Different Corneal Regions with Monocular Pterygium. (23rd March 2020) - Shen, Yun-Zhi; Xu, Mi; Sun, Song
Abstract : Purpose . To investigate the effects of pterygium on corneal cell and nerve density in patients with unilateral pterygium using in vivo laser scanning confocal microscopy (LSCM). Methods . In this cross-sectional study, 24 patients with unilateral pterygium who were treated in the Department of Ophthalmology of the Second People's Hospital of Wuxi City from April 2018 to July 2018 were analyzed. Each eye with pterygium and its fellow eye were imaged by LSCM. The density of basal corneal epithelial cells, anterior stromal cells, posterior stromal cells, dendritic cells, and endothelial cells in pterygium and adjacent clear cornea was measured. In the fellow eyes, the central cornea, nasal cornea, nasal mid-peripheral cornea, and temporal cornea were imaged. The difference in the density of cells and subepithelial nerve fibers in different corneal regions of eyes with pterygium was analyzed. The cell and nerve density of the fellow cornea were also measured to exclude the influencing factors. Results . The density of corneal basal epithelial cells in the central corneas of eyes with pterygium was 6497 ± 1776 cells/mm 2, which was higher than that in the area near the head of pterygium (5580 ± 1294 cells/mm 2, P < 0.001 ), the region above pterygium (6097 ± 1281 cells/mm 2, P = 0.049 ), and the region below pterygium (5463 ± 1007 cells/mm 2, P = 0.001 ). The density of anterior stromal cells in the central cornea was 742 ± 243 cells/mm 2, which was higher than that in the area near the head of pterygium (587 ± 189 cells/mm 2, P = 0.005 ), the region below pterygium (492 ± 159 cells/mm 2, P = 0.005 ), and the temporal cornea (574 ± 164 cells/mm 2, P = 0.003 ). The density of endothelial cells in the central cornea was 2398 ± 260 cells/mm 2, which was higher than that in the area near the head of pterygium (2296 ± 231 cells/mm 2, P = 0.011 ) and the region below pterygium (2272 ± 400 cells/mm 2, P = 0.020 ). The density of dendritic cells in the central cornea was 53 ± 48 cells/mm 2, which was lower than that in the area near the head of pterygium (250 ± 224 cells/mm 2, P = 0.001 ), the upper region (103 ± 47 cells/mm 2, P = 0.006 ), and the lower region (90 ± 48 cells/mm 2, P = 0.023 ). The corneal nerve fiber length (CNFL) in the center was higher than that in the area near the head of pterygium, the upper region, and the lower region. Compared with fellow eyes, eyes with pterygium had a significantly higher mean corneal power (KM) (P < 0.001 ). There was a significant positive linear relationship between the corneal area invaded by pterygium of pterygia and KM ( r  = 0.609, P = 0.009 ). Conclusion . Basal epithelial cells, stromal cells, endothelial cells, dendritic cells, and subepithelial nerve fibers in the central cornea of eyes with pterygium were different from those of pterygium and adjacent clear cornea. LSCM is effective for observing the morphology and quantity of corneal cells in pterygium.